Professional Development Community of Preservice Teachers for the Didactic Incorporation of Information and Communication Technologies: An Experience from Educational Design Research : Comunidad de desarrollo profesional de profesores en formación inicial para la incorporación didáctica de tecnologías de la información y las comunicaciones: una experiencia desde la investigación de diseño educativo (Papeles, 2021)
Introduction: The reflections focused on the development of digital skills in chemistry preservice teachers for the incorporation of ICT resources in didactic designs associated with a research work are presented. Methodology: With the aim of finding the didactic interactions that occur in a professional development community of preservice teachers, the intervention is conducted through a didactic unit managed from educational design research dynamics, with which information is collected from group work observations, a standardized questionnaire, and semi-structured interviews. Results and discussion: The data obtained is related to transcripts, Likert scales and open-ended questions, data that offer relevant information on the critical aspects that must be considered in the ICT training processes of science teachers. The way of working from educational design research offers the opportunity to analyze and improve the products of each of the iterative cycles developed during the training proposal. Conclusion: The results allow to recognize the categories that must be considered in the exercise of preservice teacher training (and continuous) to develop the skills of incorporation and evaluation of didactic designs supported by ICT resources.
Keywords: teacher training; didactics; ICT; science education; computer literacy